Integrative RNA-seq and CLIP-seq analysis reveals hnRNP-F regulation of TNFα/NFκB signaling in high-glucose conditions - Wang, Lan; Li, Huimeng; Guo, Xinyuan; Wang, Xiaoqin (Frontiers in Physiology, 2025)
BackgroundDiabetic kidney disease (DKD), with its complex pathogenesis, is the most important cause of end-stage renal disease and has become an urgent public health problem worldwide. Heterogeneous nuclear ribonucleoprotein F (hnRNP-F) is a member of a subfamily of widely expressed nuclear heterogeneous ribonucleoproteins with biological roles in regulating gene expression and variable splicing. Some studies have investigated hnRNP-F in DKD. However, its potential mechanism in renal intrinsic cells has rarely been reported. Therefore, it is necessary to further investigate its potential mechanism in DKD in the search for novel ideas for new therapeutic targets for DKD.MethodsIn this study, hnRNP-F was overexpressed in human renal proximal tubular epithelial (HK-2) cells cultured in high-glucose conditions, while an empty vector was transfected into HK-2 cells as a control group (NC). Meanwhile, to avoid any osmotic stress that might be caused by the use of high sugar, we also added mannose as a non-osmotic control. RNA-seq was utilized to generate transcriptome data following hnRNP-F overexpression, allowing for the analysis of differential gene expression and alternative splicing events influenced by hnRNP-F overexpression. Similarly, we overexpressed hnRNP-F in mouse podocyte clone 5 (MPC5) cells and verified the relevant indicators using Western blotting (WB) under high-glucose and high-mannitol conditions, respectively. We also downloaded the CLIP-seq data of hnRNP-F in human 293T cells from the Gene Expression Omnibus (GEO) database. Through integrative analysis of RNA-seq and CLIP-seq, we tried to identify a set of potential direct targets of hnRNP-F in cells.ResultsIn this study, RNA sequencing (RNA-seq) was utilized to demonstrate that the upregulation of hnRNP-F in HK-2 cells cultured under high-glucose conditions resulted in a substantial decrease in the expression of genes associated with the inflammatory response and suppression of the TNFα-NFκB signaling pathway. This was also verified in MPC5 cells. By analyzing CLIP-seq and RNA-seq data, we found that hnRNP-F may inhibit gene expression by binding to lncRNA SNHG1. Conversely, this upregulation led to a significant increase in alternative splicing events of genes implicated in DKD, such as hnRNPA2B1, OSML, UGT2B7, TRIP6, and IRF3. Combining CLIP-seq data, we found that hnRNP-F binds to and regulates variable splicing of the hnRNP protein family and splicing factors. This result suggests that hnRNP-F may regulate alternative splicing through the coordinated action of multiple splicing factors.ConclusionhnRNP-F has dual functions in mRNA transcriptional and post-transcriptional levels and may bind with lncRNA SNHG1 to negatively regulate the transcription of genes involved in the TNFα/NFκB signaling pathway. Meanwhile, hnRNP-F may function in the co-regulation of alternative splicing events in cells by interacting with ZFP36 to form a complex.